Beyond First-Degree Relatives: Unlocking the Genetic Insights from Extended Family History - Rungta, Archi; Kapoor, Akhil; Sarin, Rajiv (Indian Journal of Medical and Paediatric Oncology, 2025)
In oncology, a thorough family history is a cornerstone of genetic risk assessment, yet it is often limited to first-degree relatives—parents, siblings, and children—thereby missing crucial hereditary patterns. This article highlights the importance of including extended family members, such as second- and third-degree relatives, in risk assessment to uncover hereditary cancer syndromes that might otherwise go undetected. This case exemplifies how extended family history can transform patient care by enabling accurate diagnoses, personalized treatment, and preventive strategies. Despite time constraints in clinical settings, tools such as targeted questioning, standardized questionnaires, and digital pedigree platforms can streamline the collection of a three-generation pedigree. Current guidelines from the American College of Medical Genetics and Genomics and National Comprehensive Cancer Network recommend such comprehensive histories, underscoring their clinical value. Incorporating extended family history should become standard practice in oncology to align with the principles of precision medicine and improve outcomes for patients and their families.
Keywords: genetic screening; extended family history; oncology; precision medicine; hereditary cancer syndromes; three-generation pedigree